ANALISIS PENGARUH RETURN ON EQUITY, PRICE EARNING RATIO, DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI TAHUNN 2010-2012 - Dwi Sulistyowati, 10.05.52.0010; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2014)
Price Book Value (PBV) is a ratio used to quantity financial performance at a company. PBV also describe how big the market appreciate the book value of a stock. The purpose of this research is to examine the influence of return on equity (ROE), price book value (PER), debt to equity ratio (DER) toward price book value (PBV) wich is a quantity of the company value. The population this research is LQ-45 companies on 2010-2012 which on the Indonesian Stock Exchange (IDX). The sampling technique is using purposive sampling and obtain the sample of 101 companies. Company data subsequently tested with normality, multicollinearity, autocorrelation and heterokedastisity. Subsequent researchers used multiple regression to determine the relation between those variable. The results showed return on equity, price earning ratio, and debt to equity ratio significantly influence price book value with the adjustment R2of 24,20% . while individually, return on equity and price earning ratio significantly and positive influence torward price book value, while debt to equity ratio is not influence toward price book value. Keywords: return on equity, price earning ratio, debt to equity ratio and price book value